(untitled) (Al-Qamar, 2023)
This article is an introduction to life skills-based education. In this article we have defined life skills and life skills-based education. Importance and the need of life skills-based education have been defined too. We have described the methodology of life skills-based education in India and UK. The importance of life skills-based education as part of the school curriculum and the teaching of life skills in the classroom has been discussed that life skills-based education has a positive role when it is taught as a curriculum and how to apply life skills-based education to classroom setting with easy activities. In the last, the historical background of life skills-based education is briefly described.